2014
DOI: 10.1021/ed500218d
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Inquiry Skills and Self-Efficacy through Research-Inspired Modules in the General Chemistry Laboratory

Abstract: Research projects conducted by faculty in STEM departments served as the inspiration for a new curriculum of inquiry-based, multiweek laboratory modules in the general chemistry 1 course. The purpose of this curriculum redesign was to improve students' attitudes about chemistry as well as their self-efficacy and skills in performing inquiry activities. Students' ability to plan experiments and interpret data improved throughout the semester, as did their confidence in conducting research-like lab activities. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 29 publications
2
81
0
3
Order By: Relevance
“…This view falls into the “product” category of authentic research (Spell et al , 2014). Weaver et al ’s (2008) conception of authenticity was included by Winkelmann et al (2014) in the rationale for the design of a first-year chemistry “research-inspired” inquiry laboratory series, which lends weight to the idea that production of high-quality data ties to authenticity in research education.…”
Section: Theoretical Framework: Literature Definitions Of Authenticitymentioning
confidence: 99%
“…This view falls into the “product” category of authentic research (Spell et al , 2014). Weaver et al ’s (2008) conception of authenticity was included by Winkelmann et al (2014) in the rationale for the design of a first-year chemistry “research-inspired” inquiry laboratory series, which lends weight to the idea that production of high-quality data ties to authenticity in research education.…”
Section: Theoretical Framework: Literature Definitions Of Authenticitymentioning
confidence: 99%
“…Teaching materials such modules can be developed to help teachers (Paulo & Cruz, 2015). The module involves conceptual knowledge content and laboratory activities (Winkelmann et al, 2014). The module aims to facilitate student understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Additional research has examined the impacts of research-based undergraduate laboratory curricula including the CASPiE project 24−26 and other research-based curricula. 27 The body of research on the undergraduate chemistry laboratory includes reports regarding general chemistry courses, 11,12,15,18−23 organic chemistry, 13 and upper-division chemistry courses, including inorganic qualitative analysis 15 and instrumental analysis. 16,17 These previous studies have identified some important aspects of student learning in the laboratory.…”
Section: ■ Introductionmentioning
confidence: 99%